OWL Manipulation toward Building Semantic Applications and Agents - Balouchian, Pooyan; Almassian, Amin; Elci, Atilla (IEEE, 2009)
Traditional websites no longer meet the needs of today's software agents because of their unstructured nature in terms of the semantics they convey. One of the primary objectives of semantic web is to enable software agents infer facts and knowledge out of different websites. The primary aim of this project is to develop an application to manipulate OWL files, browse ontologies and enable software agents infer information semantically. Needless to say such inference is not feasible in current conventional applications. We have considered the Conference Ontology, extracted from the Ontology Repository of the University of Manchester as our sample ontology. Front architectural point of view, we used a three-layer architecture. Due to the similarity of current web applications with the architecture we used, We were able to have an actual comparison made between the two approaches.
IEEE 33rd International Computer Software and Applications Conference -- JUL 20-24, 2009 -- Seattle, WA